Phototherapy promotes healing of cutaneous wounds in undernourished rats - Saulo Nani Leite; Thiago Antônio Moretti de Andrade; Daniela dos Santos Masson-Meyers; Marcel Nani Leite; Chukuka S. Enwemeka; Marco Andrey Cipriani Frade (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Various studies have shown that phototherapy promotes the healing of cutaneous wounds. OBJECTIVE: To investigate the effect of phototherapy on healing of cutaneous wounds in nourished and undernourished rats. METHODS: Forty rats, 20 nourished plus 20 others rendered marasmus with undernourishment, were assigned to four equal groups: nourished sham, nourished Light Emitting Diode treated, undernourished sham and undernourished Light Emitting Diode treated. In the two treated groups, two 8-mm punch wounds made on the dorsum of each rat were irradiated three times per week with 3 J/cm2 sq cm of combined 660 and 890nm light; wounds in the other groups were not irradiated. Wounds were evaluated with digital photography and image analysis, either on day 7 or day 14, with biopsies obtained on day 14 for histological studies. RESULTS: Undernourishment retarded the mean healing rate of the undernourished sham wounds (p < 0.01), but not the undernourished Light emission diode treated wounds, which healed significantly faster (p < 0.001) and as fast as the two nourished groups. Histological analysis showed a smaller percentage of collagen in the undernourished sham group compared with the three other groups, thus confirming our photographic image analysis data. CONCLUSION: Phototherapy reverses the adverse healing effects of undernourishment. Similar beneficial effects may be achieved in patients with poor nutritional status.